Incidentally identified left ventricular apical aneurysm in a patient with Fabry disease. Issue 8 (29th June 2022) - Yim, Jeffrey; Gin, Kenneth; Tsang, Teresa S. M.; Luong, Christina; Lehman, Anna; Ong, Kevin; Tsang, Michael Y. C.; Jue, John; Nair, Parvathy; Nasmith, Trudy; Yeung, Darwin F.
Abstract: Fabry disease is a rare X‐linked lysosomal storage disorder caused by a deficiency in the lysosomal enzyme, galactosidase A, that can result in a progressive increase in the left ventricle (LV) wall thickness from glycosphingolipid deposition leading to myocardial fibrosis, conduction abnormalities, arrhythmias, and heart failure. We present a case of a patient with advanced Fabry cardiomyopathy, in whom a small LV apical aneurysm was incidentally discovered on abdominal imaging, which could have easily evaded detection on standard transthoracic echocardiography. The LV apex should be thoroughly interrogated in patients with Fabry cardiomyopathy, as the finding of LV aneurysm could have important management implications with respect to the prevention of stroke and sudden cardiac death.